Development of A Novel Integrated Corner Module for Narrow Urban Vehicles. (February 2019) - Rajaie, Mohammad-Amin; Khajepour, Amir; Pazooki, Alireza; Soltani, Amir
Most current urban vehicles are scaled-down versions of standard passenger cars. This imposes serious limitations on the safety, comfort, efficiency, dynamic performance and, hence, customer acceptance of the vehicle. This paper provides a unique design of an integrated corner module including an in-wheel suspension, an electrical in-wheel motor, a friction brake, a steering system, and a camber mechanism, which can be used in any urban vehicle design without modification. For the first time, a dual four-bar linkage mechanism has been designed to generate a virtual kingpin axis and provide an active camber. This approach results in a highly compact design for the corner module that can be integrated into narrow vehicles. A full-size prototype of the proposed integrated corner module has been fabricated and tested to validate the new steering mechanism and the integrated corner module characteristics.